Same-sex marriage and religious liberty : emerging conflicts - Laycock, Douglas; Picarello, Anthony R.; Wilson, Robin Fretwell (Beckett Fund for Religious Liberty ; Rowman & Littlefield Publishers, 2008)
Same-Sex Marriage and Religious Liberty explores the religious freedom implications of defining marriage to include same-sex couples. It represents the only comprehensive, scholarly appraisal to date of the church-state conflicts virtually certain to arise from the legal recognition of same-sex marriage. It explores two principal questions. First, exactly what kind of religious freedom conflicts are likely to emerge if society embraces same-sex marriage? A redefinition of marriage would impact a host of laws where marital status affects legal rights--in housing, employment, health-care, educa.